Adjusting to Globalization in Germany - Wolfgang Dauth; Sebastian Findeisen; Jens Suedekum (Institute of Labor Economics (IZA), 2018)
We study the impact of trade exposure in the job biographies, measured with daily accuracy, of 2.4 million workers in Germany. To profit from export opportunities, workers adjust through increased employer switching. Highly skilled workers benefit the most, consistent with an increase in skill demand. The incidence of import shocks falls mostly on low-skilled workers, as they are not able to adjust as well as medium- and high-skilled workers. Imports also destroy rents by workers at high-wage plants who separate from their original firm. We connect our results to the growing theoretical literature on the labor market effects of trade.
Keywords: F16; J31; R11; 330; work biographies; individual labor market responses; international trade; worker mobility; Germany